Dose of Banana Peel Liquid Organic Fertilizer on The Growth and Production of Dengdek Poek (Corchorus aestuans) - Hariyanti, Karsi; Khairani, Lizah; Susilawati, Iin (Fakultas Peternakan, Universitas Padjadjaran, 2024)
Corchorus aestuans plants have potential as animal feed. Giving banana peel POC is an effort to increase the productivity of this plant. Knowing the effect of various doses of banana peel POC on the growth and productivity of Corchorus aestuans plants is the purpose of this study. The Completely Randomized Design method was used with five treatments namely P1 = 0 ml, P2 = 100 ml, P3 = 200 ml, P4 = 300 ml, P5 = 400 ml was tested on March 21 to May 30 at the Faculty of Animal Husbandry, Universitas Padjadjaran. Each treatment was repeated four times, resulting in twenty experimental materials. Plant height, number of leaves, fresh weight, dry weight, stem leaf ratio, and shoot root ratio were some of the parameters recorded. After the data were analyzed for variance, Duncan Multiple Range Test (DMRT) was conducted. The results showed that although fresh weight was significantly affected by banana peel POC (P < 0.05), plant height, number of leaves, dry weight, stem leaf ratio, and shoot root ratio were not significantly affected (P > 0.05). The 100 ml dose was the most effective dose (P2).